More than soya alone - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Cultivation of soya and other legumes By R Nieuwenhuis & J Nieuwelink, Agromisa CTA, Agrodok 10, 2003. 88 pp. ISBN 90 77073 28 0 CTA number 1119. 5 Credit points